Financial management analysis of Culinary Micro, Small, and Medium Enterprises (MSMEs) - Putri, Arie Rachma; Husna, Faizah Khotimatul (Nur Science Institute, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are the main backbone of Indonesia's economy. The challenges MSME business operators face include product marketing, technology, financial management, capital, and human resource quality. This research aims to understand the financial management applied to culinary MSMEs located on Pabrik Karung Goni Street, Delanggu, Klaten. The research methodology employs qualitative descriptive analysis with a case study approach. Data analysis involves four financial management indicators: budget utilization, recording, reporting, and control. Data collection techniques include interviews, questionnaires, and literature review. The population in this study comprises culinary business operators in the area. The research findings indicate that the understanding of MSME operators regarding budget utilization, recording, reporting, and financial control still needs to improve. Financial management is still basic, manual, and irregularly conducted, and not all business operators report their finances. This is due to a need for more understanding and knowledge of business financial management. Therefore, further learning and understanding of financial management are needed to assess businesses' health and development better.